Beyond language boundaries : multimodal use in multilingual contexts - Fernández-Villanueva, Marta, 1965-; Jungbluth, Konstanze (Boston : De Gruyter, 2016)
In multilingual societies speakers overcome traditional language boundaries. Research on their multilingual and multimodal language use intertwines pragmatics including multimodality with cross-linguistic and transcultural perspectives. This volume links theoretical considerations with empirical evidence from data of spoken language use in Catalan, Croatian, English, German, Italian, Brazilian Portuguese, Polish and Spanish as L1, L2 or FL.